Psychological Distress Related to COVID-19 Among Nepalese Professionals: An Online Cross-sectional Study (Med Phoenix, 2020)
Background: COVID-19 is a highly infectious disease caused by SARS-CoV2 virus. It's psychological distress would be a major obstacle towards social normalcy to pre-COVID era. There were lacks of studies to assess these distresses. The aim of this study was to study psychological distress related to COVID-19 among Nepalese professionals.Methods: This online cross-sectional survey was conducted from 12th-20th, June-2020. Questionnaires were based on Corona-virus Anxiety Scale (CAS) and Obsession with COVID-19 scale (OCS).Results: Among 244 participants, majority were in the age group of 20-45 years with male female ratio of 2.1:1. About one third were health workers, 46% were teachers and service holders and remaining were from other professions. Majority of participants had subclinical obsessive (83.2%) and sub-clinical anxiety symptoms (69.3%). Law enforcement professionals (30.0%) and journalists 18.2% had highest prevalence of problematic obsessive symptoms. Law enforcement professionals (40%) had highest prevalence of problematic anxiety symptoms followed by health care workers (28.4%). About 35% of participants opted for multiple positive methods to cope with their obsessive and anxiety symptoms. Participants with higher obsession score had higher anxiety symptoms (r=0.592, p=